The Effect of Flashcard Media on Reading Literacy in Children Aged 5-6 Years: A Case Study at TK Aisyiyah 7 Ngembat Padas - Shodiq, Ummu Salamah Tyas As; Wardhani, Junita Dwi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to determine the effect of flashcard media on early reading skills among children aged 5-6 years at TK Aisyiyah Bustanul Athfal Ngembat Padas. A quantitative approach with a One-Group Pretest-Posttest design was applied, involving 15 kindergarten children from Group B as research participants. Data were collected through observation, performance tests, and documentation, and analyzed using the Wilcoxon Signed-Rank Test since the data did not meet the assumption of normality.The findings revealed a significant improvement in early reading performance following the flashcard intervention. The mean score increased from 15.33 in the pretest to 19.87 in the posttest, indicating an improvement of 29.57%. The statistical result of Asymp. Sig. (2-tailed) = 0.0006 (< 0.05) confirms that flashcard media positively and significantly affects children’s early reading proficiency. Therefore, flashcards can be recommended as an engaging, effective instructional medium for fostering foundational literacy in early childhood education.